Penggunaan Media Flashcard dalam Penguasaan Kosakata Bahasa Jerman - Indra Rosanda; Wahyu Kurniati Asri; Ambo Dalle (Academic : Journal of Social and Educational Studies, 2022)
Abstract. This research is a quasi-experimental research that aims to obtain data and information about the effectiveness of using Flashcard media in mastering German vocabulary for students of class X MIPA MAN 2 Bulukumba. The population of this study were all students of class X MIPA MAN 2 Bulukumba as many as 4 classes, then the samples were Class X MIPA 1 as the experimental class and X MIPA 3 as the control class which were selected by random sampling. The data analysis technique used t-test analysis. Based on the results of the research data analysis showed that the value of 8.45 > 2.011, with a significant level of 0.05. The results showed that the use of Flashcard media was effective in learning German vocabulary for class X MIPA students at MAN 2 Bulukumba.Keywords: Effectiveness, Flashcard Media, Vocabulary Mastery